The Strategies of Teaching Vocabulary Using Educandy Games in Senior High School Pamekasan - Alchorni, wais (Ethical Lingua: Journal of Language Teaching and Literature, 2024)
This study investigates the vocabulary of employing Educandy game as a pedagogical tool to enhance English learning strategies among senior high school students in Pamekasan. The research a case study approach, employing qualitative and quantitative methods to collect data. The integration of educandy games into language instruction is grounded in the principles of experiential learning, where students actively participate in meaningful language activities that promote language acquisition and skill development. Educandy offers a range of interactive language games that target vocabulary acquisition, comprehension, and retention through engaging gameplay and immediate feedback. A digital gamified learning platform, for high school English language instruction in Pamekasan. Specifically, the study focuses on how educandy games can enhance students' English learning strategies and vocabulary acquisition. By leveraging the interactive and game-based nature of educandy, educators aim to create a dynamic learning environment that promotes active participation, motivation, and deeper engagement with English language content. The qualitative analysis focuses on exploring students' perceptions and experiences with educandy games, while the quantitative analysis measures the impact of these games on vocabulary acquisition and learning strategy utilization. Findings reveal that eduandy games significantly improve students' engagement, motivation, and retention of vocabulary. Moreover, students demonstrate increased utilization of effective learning strategies such as mnemonic devices and contextual guessing. The study underscores the potential of gamified learning platforms like educandy in fostering language learning in high school contexts, offering insights for educators and policymakers seeking innovative approaches to language education. Keywords vocabulary information and communication technologies (ICT) Educandy games teacher strategies